21ST CENTURY SKILLS LEARNING USING LEMMANG LEARNING RESOURCES: A STUDY OF ETHNOMATHEMATICAL BUGIS MAKASSAR - Tampa, Alimuddin; Firdaus, Andi Mulawakkan; Chen, Wen-Haw; Ja’faruddin, Ja’faruddin (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract: 21st century learning demands the application of skills and knowledge that are relevant to everyday life. While mathematics is a subject taught at all levels of education, it remains challenging for many students. Often perceived as disconnected from culture, students may find learning mathematics less meaningful. This perception is partly due to the lack of integration between mathematics education in schools and cultural context. However, mathematics is inherently connected to culture, and one approach recognizing this connection is called ethnomathematics. This approach emphasizes a culture-based learning process, and has the potential to improve students' learning outcomes. One example of how culture can be used as a source of mathematics learning is through the study of the traditional food of the Bugis-Makassar ethnic heritage called